Applying the Theory of Contraints to Supply Chain Management - Simatupang, Togar Mangihut; Sandroto, Indah Victoria (Jurnal Manajemen Teknologi, 2004)
Supply chain management among independent firms often provide larger benefits form effectively satisfying customer needs and wants than working in isolation. However, many improvement initiatives often end up with devastating effects on supply chain performance. Part of the reason is sub-optimisation among the chain members resulting form a lack of awareness about the importance of the perspective of the supply chain as a whole and the existence of constraint(s). This paper applies the Theory of Constraints as a creative methodology to expose and break constraint that inhibits the chain members form progressing toward profitability. It also suggests opportunities for further research.Â Keywords:Â theory of constraints, supply chain management, and collaboration